The Reconfiguration Of The Ottoman Empire In The Concert Of Europe: Appropriation And Adaptation Of International Law In The Hamidian Era (1876-1909) - Fitriani, Anisa (PT. Student Rihlah Indonesia, 2025)
This study illuminates a crucial yet underexplored mechanism: how international legal norms were adapted to safeguard the caliphate’s legitimacy and continuity under European hegemony. It examines how the Hamidian regime both adopted and reshaped international law—as a regulatory framework and as a strategic bargaining tool to preserve dynastic survival. Drawing on a historical-critical methodology that combines primary-source archives with Ottoman intellectual discourse, this research uncovers the dialectical interaction between the Islamic legal tradition of siyar and modern international-law constructs. Findings reveal a fundamental paradox: Ottoman integration of international norms both signified subordination to European diplomatic standards and served as an adaptive realpolitik strategy amid shifting global geopolitics. By reconstructing Ottoman international relations from a non-Western perspective, the study offers historiographical innovation and yields conceptual insights for contemporary Muslim-majority states formulating foreign policy in the face of enduring hegemonic pressures.